Prevalence and risk factors for childhood obesity in Changsha and Shenzhen in China - Li, X.; Liao, B.; Liu, J.; Tan, H.; Huang, W.; Benjamin, A.; Liu, W.; Huang, X.; Wen, S. (Zhong Nan Da Xue Xue Bao Yi Xue Ban, 2010)
Objective: To determine the prevalence and the risk factors for childhood obesity in Changsha and Shenzhen, China. Methods: A case-control study was conducted in 209 obese children (the cases) identified in the investigation on childhood obesity in 6 288 children aged 6 to 9 years in Changsha and Shenzhen in China and 209 children with normal weight (the controls). The cases and controls were matched by gender, age, and school. Adjusted odds ratio (aOR) and 95% confidence intervals (CI) for the risk factors were measured. Results: The prevalence rate of overweight and obese children was 9.28% and 3.30% in Changsha, and 12.17% and 4.22% in Shenzhen, respectively. The rate of overweight children is significantly higher in Shenzhen than in Changsha. No statistical difference was observed in the rate of obesity between the children in both cities. Paternal obesity (OR 1.78, 95% CI 1.01 to 3.16), maternal weight gain during pregnancy>or=15.0 kg (OR 5.22, 95% CI 2.78 to 9.80), birth weight>or=4.00 kg (OR 2.55, 95% CI 1.24 to 5.26), unhealthy snacks>or=1 per week (OR 3.94, 95% CI 1.11 to 13.99), and watching television>or=2 hours per day(OR 2.35, 95% CI 1.01 to 5.47) were associated with childhood obesity when potential confounding factors were adjusted by multi-variable logistic regression analysis. Conclusion: Paternal obesity, gestational weight gain, high birth weight, and unhealthy life-style are important risk factors for obesity in urban children in south China.